2016
DOI: 10.1680/jenge.15.00020
|View full text |Cite
|
Sign up to set email alerts
|

Model tests of energy piles with and without a vertical load

Abstract: The thermomechanical behaviour of energy piles during heating and cooling through model tests was studied. These model tests were carried out both with and without a vertical load and dry sand was used. The axial load distribution, load-settlement of the pile head, pile and soil temperature, soil pressure at the pile tip, horizontal soil pressure, thermal stress and mobilised side shear stress were investigated. The magnitude of stress and displacement influenced by vertical load or no load was comparatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A number of small-scale physical model studies have characterized the axial thermal response of energy piles for monotonic heating (McCartney and Rosenberg, 2011;Ng et al, 2014b;Goode and McCartney, 2015) and cyclic temperatures (Kalantidou et al, 2012;Ng et al, 2014a;Stewart and McCartney, 2014;Yavari et al, 2014Yavari et al, , 2016aNg et al, 2016;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of small-scale physical model studies have characterized the axial thermal response of energy piles for monotonic heating (McCartney and Rosenberg, 2011;Ng et al, 2014b;Goode and McCartney, 2015) and cyclic temperatures (Kalantidou et al, 2012;Ng et al, 2014a;Stewart and McCartney, 2014;Yavari et al, 2014Yavari et al, , 2016aNg et al, 2016;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for the stable responses of the thermal strains towards the end of experiments is that there were no head loads on the pile or end restraints in the present study. According to some physical model studies with thermal cycles on energy piles (Kalantidou et al, 2012;Stewart and McCartney, 2013, Yavari et al, 2014, 2016aWang et al, 2016), thermally induced settlement is reversible for pile head loads corresponding to as low as 20% of the pile ultimate resistance, and becomes irreversible for higher pile loads, particularly for loads closer to the ultimate pile resistance. However, the soil type plays an important role in the thermal response of the pile, and the dense sand at the current site likely contributed to the relatively high resistance to axial thermal deformations.…”
mentioning
confidence: 99%
“…The comparison of load-settlement profile with Wang et al [22] was shown in Figure 7. The bearing capacities of the PEP and solid energy pile both decreased with the decreasing temperature.…”
Section: Comparison Of Load-settlement Relationships With Solidmentioning
confidence: 94%
“…The change of energy pile bearing characteristic was subjected to the restraint conditions of the tested piles, and it was also found that the use of energy piles causes significant thermally induced additional deformation in the pile itself [7][8][9][10]. Model tests were also carried out to examine the heat transfer performance and bearing characteristics of piles with embedded tubes under normal working conditions over repeated temperature cycling, and the results show that the thermal stresses were superimposed with the mechanical stresses [11][12][13][14]. Centrifuge modeling of soilstructure interaction in energy foundations was also carried out to measure the transient thermomechanical response of end-bearing energy pile during heating-cooling cycles, and the result shown that the model pile was affected by the heating and cooling cycles [15,16], being consistent with the conclusion that the effect of temperature on the shear strength of sand, clay, and the clay-concrete interface is negligible [17,18].…”
Section: Introductionmentioning
confidence: 99%